ETR : Mr Steak House / Fatin Umiera Rohaizan ... [et al.] - Rohaizan, Fatin Umiera; Md Hashim, Mohammad Hafizee; Ariffin, Muhammad Fuad; Razali, Muhammad Zaid; Syed Amran, Syed Zul Hafiz (2018)
Nowadays most of Malaysian looks for something unique and interesting place to eat. It is the right place, we provide unique combination of excellent food at value pricing with a fun relax and entertaining atmosphere. Decoration with modern concept and family friendly environment. Most importantly all of the products are certified HALAL by the Islamic Affairs Division, Department of the JAKIM, Malaysia. Future prospect is corporate sectors to choose our place for their small event and function at our place.